TEACHERS’ PERCEPTIONS ABOUT THE PEDAGOGICAL CONTENTS OF AN EFL TEXTBOOK - EMMI KURWANTI (Journal of English Education Program (JEEP), 2015)
This research investigated the English teachers’ perceptions about the pedagogical contents of an EFL textbook ‘English in Focus’. This descriptive study was conducted to investigate teachers’ perceptions about the pedagogical contents of an EFL textbook ‘English in Focus’ of a Junior High School in Cimanggu. Two English teachers of a junior high school in Cimanggu were selected as a sample of the research. A questionnaire was chosen as the research instrument to answer the first and the second research questions. To analyze the data, exploratory data analysis was used in this research which was adapted from Cohen, et al. (2007, p. 98). The research findings showed that the pedagogical contents of an EFL textbook ‘English in Focus’ was taught by the English teachers to junior high school students. Besides, the research findings also showed that the English teachers perceived the materials of an EFL textbook ‘English in Focus’ could fulfilled the criteria of the pedagogical contents. Furthermore, the results of this research may give a broader knowledge about teaching learning process to readers. Keywords: teachers’ perceptions, the pedagogical contents, an EFL textbook.